Comparative Analysis of Fast and Standard Charging Technologies: Implications for Mobile Device Efficiency and Usage - Taufik, Muhammad; Sutrio, Sutrio (Jurnal Ilmiah Profesi Pendidikan, 2024)
The growing demand for efficient mobile device charging technologies has led to the widespread adoption of fast charging solutions. This study compares the performance of fast and standard charging methods on mobile devices, focusing on key factors such as charging time and energy efficiency. Through simulations conducted on three popular phone models, we found that fast charging significantly reduces charging time by approximately 48%, yet only marginally impacts energy efficiency. This study suggests that fast charging offers substantial convenience without a significant trade-off in energy consumption, highlighting its potential in future mobile device design and user behavior.